Penguatan Manajemen Kelembagaan Masjid Nurul Huda di Desa Nambi Melalui Pelatihan Administrasi dan Keuangan - Rosyidi, Muh. Hasyim; Chotibuddin, M.; Abidah, Zakiyatul; Maghfur, Arif; Solechan, Solechan (Bakti Insani: Jurnal Pengabdian dan Pemberdayaan, 2025)
As centers of religious and social activities, mosques play a strategic role in fostering the community and developing the community, requiring professional and accountable management to optimize their function. However, many mosques in rural areas still face challenges in institutional management, particularly in poorly systematized administrative and financial management. The Nurul Huda Mosque in Nambi Village is one such mosque that serves as a center for local community religious activities, yet in practice it still faces various problems related to organizational governance. Manual administrative management, disorganized financial records, and a lack of understanding of modern management principles among the administrators are challenges that must be addressed immediately to increase congregational trust and participation. The purpose of this community service program is to strengthen the institutional management capacity of the Nurul Huda Mosque through administrative and financial training programs for mosque administrators, resulting in more professional, transparent, and accountable governance to support the sustainability of mosque operations and improve the quality of services to the congregation